2008
DOI: 10.3409/azc.51a_1-2.35-47
|View full text |Cite
|
Sign up to set email alerts
|

Breeding biology and ecology of Whinchat Saxicola rubetra on abandoned farmland of Opole Province (SW Poland)

Abstract: In 2003-2007 the breeding biology and ecology of Whinchat Saxicola rubetra were investigated on the 500 ha mosaic agricultural landscape (cropland, abandoned cropland, meadows, pastures and young pine plantations) in SW Poland. In the area of uncultivated fields, meadows and pine plantations 36, 34, 31, 27 and 28 pairs bred consecutively in particular seasons of the study period. Most nests were situated in the abandoned fields in the grass and tansy Tanacetum vulgare. In the studied population the median date… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 6 publications
1
11
2
Order By: Relevance
“…In our study population the average distance of a flight from the nest by parent Whinchats was 33 m [±SD 21.2 m, range 4-80 m (Frankiewicz 2008)]. This value was smaller compared with previous data for Whinchats foraging in extensive grasslands in Sweden [43.8 m (Andersson 1981)] or Alpine meadows in Switzerland [42.2-54.7 m (Britschgi et al 2006)].…”
Section: Methodscontrasting
confidence: 62%
See 2 more Smart Citations
“…In our study population the average distance of a flight from the nest by parent Whinchats was 33 m [±SD 21.2 m, range 4-80 m (Frankiewicz 2008)]. This value was smaller compared with previous data for Whinchats foraging in extensive grasslands in Sweden [43.8 m (Andersson 1981)] or Alpine meadows in Switzerland [42.2-54.7 m (Britschgi et al 2006)].…”
Section: Methodscontrasting
confidence: 62%
“…500-ha area of agricultural landscape in south-west Poland (Frankiewicz 2008(Frankiewicz , 2010(Frankiewicz , 2015. The dominant form of land use in the region was arable, with crop fields covering about 87-93 % of the total area studied.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the Ochil Hills study area, no influence of the measured habitat was apparent on the likelihood of an area being occupied by Whinchats. At the time of the survey, this site with ungrazed and a developing ground vegetation would be comparable to abandoned, derelict or fallow farmland that can be favoured by Whinchats elsewhere in Europe (Ruttledge & Scott 1978, Frankiewicz 2008, Orowski 2010 with the additional advantage of abundant song perches and vantage points for foraging in the form of young planted trees. Given the relatively high density of territories within the study area, it can be assumed that overall conditions were favourable for them.…”
Section: Territory Attributesmentioning
confidence: 99%
“…Whinchats Saxicola rubetra are an example of one species that was formerly widespread across European lowlands where it was considered to be a bird typical of semi-natural grasslands and meadows. In many areas it is now confined to upland meadows, where grass cutting dates have not advanced as a result of agricultural intensification (Müller et al 2005, Bolliger et al 2007, Broyer 2009), and also abandoned or derelict agricultural land provides extensive areas of uncut grassland (Frankiewicz 2008, Orowski 2010. Increased nest losses and greater mortality of incubating females attributable to the earlier cutting of meadows (Gruebler et al 2008) and reduced food availability (Britschgi et al 2006) have been identified as causal mechanisms produced by agricultural intensification that have lead to population declines and range contractions of Whinchats.…”
mentioning
confidence: 99%